Room at the margins for energy-crops? A qualitative analysis of stakeholder views on the use of marginal land for biomass production in Denmark. (April 2019) - Shortall, O.K.; Anker, Helle Tegner; Sandøe, Peter; Gamborg, Christian
Abstract: Greater production of agricultural biomass for energy generation means a greater overlap between the energy and agricultural value chains. The production of biofuels from food crops was previously criticised as conflicting with food production. Use of so-called 'marginal land' is proposed to overcome previous controversies. Using interviews and document analysis, this paper explores the meaning of 'marginal land' for non-food energy crop production in Denmark and conflicts that arose over its proposed use. In Denmark there was a different conception of marginal land – environmentally sensitive land where intensive cultivation causes impacts. Policies were put in place to promote the use of this 'environmentally marginal land'. However, competing environmental objectives for this land – for different types of biodiversity, ecosystems services and aesthetic preferences meant these policies were repealed. The paper shows how discussions of biomass production on agricultural land, and particularly marginal land, reflect the nuances of competing land uses in agriculturally intensive countries like Denmark. It is not only a matter of trade-offs between different types of agricultural production, such as food and fuel, or between environmental benefits and production, but over the optimal environmental use of the land to achieve multifunctional benefits. As well as questions of equity, access and practicality, the marginal land debate in agriculturally intensive countries needs to include questions of appropriate and desired environmental outcomes and means of stakeholder engagement to establish these. Highlights: Growing biomass on marginal land is seen to overcome 'food versus fuel' debates. Danish stakeholders identified marginal land as environmentally sensitive land. Growing biomass on 'environmentally marginal' land creates environmental benefits. Use of this land for biomass was resisted due to landscape and biodiversity change. 'Marginal land' debates should include symbolic and aesthetic land use dimensions.